2023
DOI: 10.1186/s13033-023-00573-y
|View full text |Cite
|
Sign up to set email alerts
|

Bi-stability and critical transitions in mental health care systems: a model-based analysis

Abstract: Background Delayed initiation and early discontinuation of treatment due to limited availability and accessibility of services may often result in people with mild or moderate mental disorders developing more severe disorders, leading to an increase in demand for specialised care that would be expected to further restrict service availability and accessibility (due to increased waiting times, higher out-of-pocket costs, etc.). Methods We developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Treatment dependent recovery is most effective where existing services provide personalised measured care via the use of technology and coordinated care to reduce mental health progression 44 . Skinner et al identified the need for modifying service availability and accessibility of mental health care systems to increase early recovery rates and reduce the proportion of people whose condition declines 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment dependent recovery is most effective where existing services provide personalised measured care via the use of technology and coordinated care to reduce mental health progression 44 . Skinner et al identified the need for modifying service availability and accessibility of mental health care systems to increase early recovery rates and reduce the proportion of people whose condition declines 44 .…”
Section: Discussionmentioning
confidence: 99%